Numerical investigation of rotating cavitation in a three blade inducer. Issue 1 (1st April 2022) - Mu, Zhendong; Chen, Tairan; Liang, Wendong
Abstract: The rotating cavitation in the inducer has a crucial influence on the safety and operation efficiency of heavy-duty liquid rocket engines. The objective of this paper is to investigate the rotating cavitation behaviors in the inducer and the influence of thermodynamic effects on the inducer performance, under a wide range of operating conditions. The cavitating flows through a three-blade inducer with room temperature water and liquid oxygen was numerically investigated. The numerical approaches considering the thermal effects are verified by the experimental data. The results show that as the inlet pressure decreases, cavity firstly grows near the blade tip clearance and extends to the blade surface. As the pressure further decreases, the cavity volume becomes larger and blocks the entire flows passage. It causes the dramatic drop of head performance of inducer. A periodical evolution of cavity volume in each blade was analyzed. The characteristic frequency and radial force amplitude of rotating cavitation generally agreed with the experimental measurements. The results show that the variation of radial force on the hub is related to the evolution of the cavity area. At the same cavitation number and flow rate coefficient, the breakdown point of liquid oxygen is later than that of room temperature water due to the thermodynamic effects.